Bifurcation Characteristics Analysis of Gear System Considering Time-varying Gear Backlash - Liu, Jiahao; Liu, Chengyu; Mo, Guoyin; Liu, Fuhao (International Journal of Mechanical and Electrical Engineering, 2024)
Dynamical models for super gear systems have been established, considering both fixed gear backlash and time-varying gear backlash. The focus is on analyzing the modeling process of the time-varying gear backlash. Based on this, a six degrees of freedom bending-twisting dynamical model for super gears has been developed. Then, using rotational speed as the control variable, numerical simulations have been conducted to compare the bifurcation characteristics of super gear systems with fixed gear backlash and time-varying gear backlash. The results indicate that the overall trends of the bifurcation characteristics for both systems are consistent, with their vibration periods decreasing as the rotational speed increases, leading to a gradual stabilization of the system. However, the bifurcation characteristics of the super gear system considering the time-varying gear backlash exhibit a distinct leading trend, showing significant jump phenomena at relatively low rotational speeds.